Integrity of the DNA and Cellular Ultrastructure of Cryptoendolithic Fungi in Space or Mars Conditions: A 1.5-Year Study at the International Space Station. - Onofri, S.; Selbmann, L.; Pacelli, C.; de Vera, Jean Pierre Paul; Horneck, G.; Hallsworth, J.E.; Zucconi, L. (Life, 2018)
The black fungi Cryomyces antarcticus and Cryomyces minteri are highly melanized and are resilient to cold, ultra-violet, ionizing radiation and other extreme conditions. These microorganisms were isolated from cryptoendolithic microbial communities in the McMurdo Dry Valleys (Antarctica) and studied in Low Earth Orbit (LEO), using the EXPOSE-E facility on the International Space Station (ISS). Previously, it was demonstrated that C. antarcticus and C. minteri survive the hostile conditions of space (vacuum, temperature fluctuations, and the full spectrum of extraterrestrial solar electromagnetic radiation), as well as Mars conditions that were simulated in space for a 1.5-year period. Here, we qualitatively and quantitatively characterize damage to DNA and cellular ultrastructure in desiccated cells of these two species, within the frame of the same experiment. The DNA and cells of C. antarcticus exhibited a higher resistance than those of C. minteri. This is presumably attributable to the thicker (melanized) cell wall of the former. Generally, DNA was readily detected (by PCR) regardless of exposure conditions or fungal species, but the C. minteri DNA had been more-extensively mutated. We discuss the implications for using DNA, when properly shielded, as a biosignature of recently extinct or extant life.